Sonographic evaluation of median nerve cross‐sectional area in a normal Iranian population: A cross‐sectional study - Seyed Mansoor Rayegani; Masume Bayat (Health Science Reports, 2023)
Abstract Introduction Considering disagreements on the normal range of median nerve cross‐sectional area (MNCSA) and insufficient data in the Iranian population, this study aimed to measure normal MNCSA. Methods In this cross‐sectional study, bilateral upper limbs of 99 subjects were assessed by sonography, and MNCSA was measured at three levels: forearm, carpal tunnel inlet (CTI), and carpal tunnel outlet (CTO). The association between MNCSA and demographic factors was assessed. Results Mean MNCSA was 6.33 mm2 at the forearm, 9.41 mm2 at CTI, and 10.67 mm2 at CTO. MNCSA was significantly higher in males (6.78 vs. 5.94 mm2 at the forearm, 9.98 vs. 8.92 mm2 at CTI, and 11.24 vs. 10.84 mm2 at CTO in males and females, respectively) and taller (>170 cm) subjects in all three levels (6.69 vs. 6.03 mm2 at the forearm, 9.80 vs. 9.02 mm2 at CTI, and 11.27 vs. 10.12 mm2 at CTO in taller and shorter subjects, respectively). MNCSA was not significantly associated with wrist ratio (WR) or body mass index (BMI). Conclusion The normal MNCSA range in the Iranian population is 6.31 mm2 (forearm) to 10.74 mm2 (CTO). MNCSA is significantly higher in males and taller subjects but is not associated with BMI and WR.